We can solve the equation 7(2x+9) = 14x+9 to get 0 = -54, which is a contradiction. Therefore, the expressions cannot be equivalent.
Jesse is incorrect. The expressions 7(2x + 9) and 14x + 9 are not equivalent.
To see this, let's distribute the 7 in the first expression:
7(2x + 9) = 14x + 63
Now, let's subtract 63 from both sides of the equation:
14x + 63 - 63 = 14x + 9 - 63
This simplifies to:
14x = 14x - 54
Finally, let's subtract 14x from both sides of the equation:
14x - 14x = 14x - 54 - 14x
This simplifies to:
0 = -54
This is a contradiction, so the expressions 7(2x + 9) and 14x + 9 cannot be equivalent.